2015
DOI: 10.1631/jzus.b1400192
|View full text |Cite
|
Sign up to set email alerts
|

Growth effects of botulinum toxin type A injected unilaterally into the masseter muscle of developing rats

Abstract: Abstract:Objective: To evaluate the effects of botulinum toxin type A (BTX-A) on mandible skeletal development by inducing muscle hypofunction. Methods: Four-week-old Sprague-Dawley rats (n=60) were divided into three groups: Group 1 animals served as controls and were injected with saline; Group 2 animals were injected unilaterally with BTX-A (the contralateral side was injected with saline); and Group 3 animals were injected bilaterally with BTX-A. In Group 2, the saline-injected side was designated the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…As reported by other scholars, subchondral bone, cortical bone, alveolar bone, and even the growth of the mandible were influenced by loading as well [ 25 27 ]. However, it is still unclear how much decreased loading could consistently lead to a bone defect.…”
Section: Discussionmentioning
confidence: 78%
“…As reported by other scholars, subchondral bone, cortical bone, alveolar bone, and even the growth of the mandible were influenced by loading as well [ 25 27 ]. However, it is still unclear how much decreased loading could consistently lead to a bone defect.…”
Section: Discussionmentioning
confidence: 78%
“…Efficacy and safety of BoNT-A depend on dose and application and should be adjusted based on indication and clinical assessment. In animal studies, described long-term effects on the muscular skeletal system, in the sense of degradation, underline the need for moderate dosages in an elaborated treatment strategy such as the key-muscle concept [ 96 , 97 ]. Dose optimisation and best practice in application are crucial.…”
Section: Optimising Injectionmentioning
confidence: 99%
“…Considering that muscle contraction drives the mechano-transduction and molecular signaling required for bone homeostasis, what happens to mandibular bone when masticatory muscles are paralyzed? Pre-clinical evidence showed that masticatory muscle atrophy induced by BoNT/A impairs craniofacial bone development by reducing the size of particular regions of mandible (such as mandibular condyle) and altering its morphology, when compared with normally developed individuals [ 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. However, the adverse effects of this intervention in adult individuals remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%